Academic Writing Anxiety on Undergraduate Thesis Writing - Shobari, Rifani; Qalyubi, Imam; Widiastuty, Hesty (IKIP Siliwangi, 2025)
Academic writing anxiety is a common barrier for undergraduates, particularly during thesis writing, impacting both performance and well-being. While general writing anxiety has been studied, this research focuses specifically on thesis writing. The study aims to identify factors contributing to academic writing anxiety in students and the symptoms they experience. Using a phenomenological qualitative approach, in-depth semi-structured interviews were conducted with 12 participants from the English Language Education program at the State Islamic Institute of Palangka Raya, all of whom had taken a thesis course. The researcher adapted the SWLAI instrument for data collection and applied content analysis to interpret the results. Findings reveal that factors such as fear, high or low expectations, self-esteem, lack of ability, stress, and communication issues with lecturers contribute to anxiety. Common symptoms include physical disturbances and avoidance behaviors. The results of this research findings are expected to be a consideration for various parties to arrange the best way to prevent or handle anxiety in the implementation of thesis writing as a final project.